Direction Based Routing for Mobile Ad Hoc Networks - Nedos, Andronikos (Trinity College Dublin. Department of Computer Science, 2001)
A Mobile Ad Hoc Network is comprised of nodes with wireless interfaces that are able to move arbitrarily, changing the network topology as they do so. Designing a routing protocol for such a network, where connections can be broken and reestablished with different paths is challenging and a standard routing scheme has yet to emerge.

Routing protocols for Mobile Ad Hoc Networks have so far taken approaches similar to routing protocols used for traditional wired non mobile networks. Variations of link state or source routing protocols or combinations of both have been proposed. Recently, a class of protocols that exploit the physical location of mobile nodes for more efficient routing of data has appeared. The subject of this thesis is related to such location aware protocols.

We argue that by taking advantage of the location and the mobility path nodes follow, routing can be improved. We identify and explore a number of algorithms that can provide a metric for similarity of direction. One of these metrics is then implemented in a simulation environment (ns) using the Dynamic Source Routing (DSR) protocol. The protocol is then tested with mobility scenarios and communication patterns and results are extracted that compare its performance against the original DSR protocol. The three performance metrics that are evaluated from the simulation results include the longevity of routes, the routing efficiency and the channel usage of the protocol. Results have proved no significant performance gains of the Direction Based DSR against the standard DSR, but have shown scalability problems associated with DSR in densely populated networks.
Keywords: Computer Science